2019
DOI: 10.1107/s1600577519011299
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of sample preparation protocols of soft biological tissues for morphometric studies using synchrotron-based X-ray microtomography

Abstract: The spread of microtomography as a tool for visualization of soft tissues has had a significant impact on a better understanding of complex biological systems. This technique allows a detailed three-dimensional quantitative view of the specimen to be obtained, correlating its morphological organization with its function, providing valuable insights on the functionality of the tissue. Regularly overlooked, but of great importance, proper sample mounting and preparation are fundamental for achieving the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Recent studies have shown the importance of systematically studying the effect of different types of sample preparation protocols and imaging conditions to best describe the inner structure of complex soft biological tissues 21 , 33 , 41 . Fresh frozen samples imaged in saline solution enable conditions close to native.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the importance of systematically studying the effect of different types of sample preparation protocols and imaging conditions to best describe the inner structure of complex soft biological tissues 21 , 33 , 41 . Fresh frozen samples imaged in saline solution enable conditions close to native.…”
Section: Introductionmentioning
confidence: 99%
“…dehydration from the beam during imaging and sample micro-movements can reduce the image quality 33 . Fixation of the tissue can increase stability, but the images could still be affected by vibrations 41 . Samples embedded in solid media are generally more stable during imaging, but they require more invasive preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, some differences in the average size of the secretory structures were observed when measured by X-ray MicroCT or HRLM images. This effect could be linked to distortions originating in sample preparation procedures, including sample dehydration and resin embedding, meaning all quantitative comparisons between specimens should be made under the same imaging method 53 . Results obtained from both imaging methods are complementary in terms of a more exhaustive analysis of morphological characteristics of plant remains.…”
Section: Discussionmentioning
confidence: 99%
“…High z-probes are contrast agents featuring high-atomic-number (high-Z) elements which absorb x-rays effectively. Examples of these probes that have already been reported for visualizing biological microstructures include osmium (Ananda et al, 2006;Johnson et al, 2006;Litzlbauer et al, 2006;Dias et al, 2019), gold (Mizutani et al, 2007(Mizutani et al, , 2008(Mizutani et al, , 2010Li et al, 2010), silver (Mizutani et al, 2008;Parameswaran et al, 2009), iodine (de Crespigny et al, 2008;Metscher, 2009), platinum (Wang et al, 2017), mercury (Fonseca et al, 2018;Nani et al, 2020), tungsten (Metscher, 2009), and lead (Kamenz and Weidemann, 2009). The advantage of this method is the clear visualization of structures that may not be well delimited only by phase contrast.…”
Section: X-ray Absorption Microtomography Using High-z Probesmentioning
confidence: 99%
“…All these approaches rule out the need for fluorescence dyes and complex sample preparation. Nonetheless, XRM is still in an initial state of development creating the necessary tools focusing not only on instrumentation but also on sample preparation and mounting protocols (Dias et al, 2019).…”
Section: Perspectives Instrumentationmentioning
confidence: 99%